Structural model and properties of AdoMetDc domain of the bifunctional Plasmodium falciparum S-adenosylmethionine decarboxylase/Ornithine decarboxylase - Louw, Abraham Izak (University of Pretoria, 2013)
Dissertation (MSc(Biochemistry))--University of Pretoria, 2004.